Potential of Ocean Wave Energy in the Northern Waters of Central Java as a Renewable Energy Source - Nugroho, Anendha Destantyo (Indonesian Journal Publisher, 2025)
Global efforts to reduce reliance on fossil fuels and greenhouse gas emissions increasingly emphasize the potential of marine energy as a renewable resource. This study analyzes the characteristics of significant wave height and estimates of wave energy and wave power in the northern waters of Central Java, Indonesia, during 2024. ERA5 reanalysis data from the European Centre for Medium-Range Weather Forecasts (ECMWF) were processed using Python to generate monthly maps of wave height and wave energy, daily time series of energy and power, and boxplots of monthly wave-energy distribution. The annual significant wave height ranged from 0.1 to 1.6 m, with the highest values occurring in December and March and the lowest in April and November. Monthly wave energy exceeded 1,200 J m⁻², while daily wave-energy density reached up to 3,000 J m⁻² and daily wave power peaked near 6 kW m⁻¹ during the west monsoon season. The highest variability occurred in March and December, reflecting the influence of monsoonal wind forcing. These findings demonstrate that the northern Central Java Sea has promising, relatively stable wave-energy potential, particularly during the west monsoon. They may contribute to Indonesia’s clean-energy transition, coastal resilience, and small-island electrification, in alignment with Sustainable Development Goals 7 and 13.